Pengembangan Pariwisata Berbasis Masyarakat (Community Based Tourism) di Desa Pekasiran Kecamatan Batur Kabupaten Banjarnegara - Moch. Agus Syadad Saefullah; Ridwan Iskandar; Budi Wibowo; M. Romi Okta Viano; Gilang Ramadhan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In achieving the target of tourism contribution to GDP which reaches 12%, several tourism development strategies are needed. This research aims to determine how the development of community based tourism in Pekasiran Village. This research uses a qualitative approach with a case study method. In this research, it is more focused on village government, local communities, and POKDARWIS. The results research is that the village government carried out its role by facilitating the formation of Pokdarwis and taking policies in terms of the distribution of benefits and the results of managing tourism objects in the form of economic improvement. Pokdarwis carries out the role by encouraging and motivating the community to develop tourism objects. Local communities are also involved in planning and decision-making in the process of developing tourism objects, which in this case means that the tourism development process in Pekasiran Village has involved the active participation of the surrounding community.